A Statistical Study on DH CMEs and Its Geoeffectiveness. (24th December 2013) - Vasanth, V.; Umapathy, S.
Abstract : A detailed investigation on geoeffectiveness of CMEs associated with DH-type-II bursts observed during 1997–2008 is presented. The collected sample events are divided into two groups based on their association with CMEs related to geomagnetic storms Dst ≤−50 nT, namely, (i) geoeffective events and (ii) nongeoeffective events. We found that the geoeffective events have high starting frequency, low ending frequency, long duration, wider bandwidth, energetic flares, and CMEs than nongeoeffective events. The geoeffective events are found to have intense geomagnetic storm with mean Dst index (−150 nT). There exists good correlation between the properties of CMEs and flares for geoeffective events, while no clear correlation exists for nongeoeffective events. There exists a weak correlation for geoeffective events between (i) CME speed and Dst index ( R = - 0.51 ) and good correlation between (i) CME speed and solar wind speed ( R = 0.60 ), (ii) Dst index and solar wind speed ( R = - 0.64 ), and (iii) Dst index and southward magnetic field component (B z ) ( R = 0.80 ) . From our study we conclude that the intense and long duration southward magnetic field component (B z ) and fast solar wind speed are responsible for geomagnetic storms, and the geomagnetic storms weakly depend on CME speed. About 22% (50/230) of the DH-type-II bursts are associated with geomagnetic storms. Therefore the DH-type-II bursts associated with energetic flares and CMEs are good indicator of geomagnetic storms.